Line-of-sight acceleration as a test of the Galactic Yukawa potential - da Silva Barbosa, Felipe A.; Amendola, Luca; Rodrigues, Davi C.; Capuzzo-Dolcetta, Roberto (Physics of the Dark Universe, 2025)
We forecast the impact of direct radial acceleration measurements, based on two redshift measurements of the same target one decade apart, on constraining the Yukawa correction to the Newtonian potential in the Milky Way. The Galaxy’s matter distribution is modeled as the sum of a spherical bulge, a spherical dark matter halo, and two axially symmetric disks. Considering a sample of 165 Milky Way globular clusters, we find that the precision of next-generation spectrographs (∼ 10 cm s−1) is not sufficient to provide competitive constraints compared to rotation curve data using the same baryonic matter distribution. The latter sample only becomes competitive for a precision better than 0.6 cm s−1. On the other hand, we find that adopting a population of 1.3×105 RR Lyrae stars as targets, a precision of ∼ 10 cm s−1 can achieve constraints on the Yukawa parameters as strong as with the rotation curves.